Spleen Autotransplantation In Rat - Adlina Mohammad; Affirul Chairil Ariffin; Wan Omar Abdullah; Asral Wirda Ahmad Asnawi; Fadlul Azim Fauzi Mansur; Anuar Sani; Razrim Rahim (Faz Publishing, 2024)
Non-Indexed Publication